Methane-rich gas emissions from natural geologic seeps can be chemically distinguished from anthropogenic leaks - Lisa J. Molofsky; Giuseppe Etiope; Daniel C. Segal; Mark A. Engle (Communications Earth & Environment)
Abstract Fossil methane, a key component of the atmospheric greenhouse gas budget, is emitted by fugitive leaks from petroleum industry activities and natural geologic seepage. Since the gas from these two sources can exhibit similar isotopic compositions, differentiating them using atmospheric observations is often challenging. Here, we provide a conceptual model that helps distinguish the two sources. Using molecular and isotopic data from global seep and reservoir gas inventories, and new seep analyses from major hydrocarbon-bearing basins in California, we identify six post-genetic changes in gas chemistry. These changes include alterations of molecular ratios among alkanes (ethane, propane, and butane) and 13C enrichment of propane and carbon dioxide due to oxidation and secondary methanogenesis. Such changes are typical of seepage, and do not occur in deep reservoir gas that may leak during extraction and transport. Our model can aid in source attribution of fossil gas analyzed in airborne or field surveys and serve as a foundation for future work on regional emissions of natural gas.